Shape measurement using one frame projected sawtooth fringe pattern - Chen, Lujie (2011)
Fringe projection technique is a non-contact, full field shape measurement method. The object depth information is recorded as sinusoidal or square wave fringe patterns. The phase-shifting technique or Fourier transform method can be used to extract wrapped phase data and a continuous phase distribution can be retrieved by a phase unwrapping process. In this paper, a shape measurement method using one frame projected sawtooth fringe pattern is proposed. A computer-generated sawtooth pattern is projected by a programmable liquid crystal display (LCD) projector. The deformed sawtooth pattern encoding object shape is converted to a wrapped phase map without using phase shifting or Fourier transform and a continuous phase distribution is retrieved by a quality-guided phase unwrapping algorithm. A special phase quality map, capable of detecting invalid shadowed phase data, is proposed to facilitate the unwrapping process.